Adrenal function testing following hormone therapy for infantile spasms: case series and review of literature - John R Mytinger; Sasigarn A Bowden (Frontiers in Neurology, 2015)
Prednisolone and adrenocorticotropic hormone (ACTH) are hormone therapies for infantile spasms. There is limited data on the occurrence of decreased adrenal reserve or signs of clinical adrenal insufficiency after hormone therapy. This is a retrospective medical record review of patients referred to our Infantile Spasms Program. Our standardized infantile spasms management guideline began in September 2012 and initially included a post-hormone laboratory assessment of adrenal function. Medical records were assessed for hormone treatments, adrenal function testing, and signs of adrenal insufficiency. Forty-two patients who received one or both hormone therapies met inclusion criteria. A post-hormone laboratory assessment of adrenal function was done in 14 patients. Of these 14 patients, two had an abnormal laboratory assessment of adrenal function, both by adrenal stimulation testing – one after ACTH and one after prednisolone. One patient received hydrocortisone replacement and the other received stress dose hydrocortisone as needed; neither patient developed signs of adrenal insufficiency. Another patient treated with both types of hormone therapy in tandem, who did not have a post-hormone laboratory assessment, developed signs of mild adrenal insufficiency and required replacement hydrocortisone. Our study suggests that adrenal suppression can occur after modern hormone therapy regimens. We found two patients with abnormal adrenal function testing after hormone therapy and another patient with signs adrenal insufficiency. Given the seriousness of adrenal crisis, caregiver education on the signs of adrenal insufficiency is critical. Greater vigilance may be indicated in patients receiving both types of hormone therapy in tandem. Although a routine post-hormone laboratory assessment of adrenal function may not be feasible in all patients, replacement or stress dose hydrocortisone is necessary for all patients with suspected adrenal insufficiency.